Paediatric Measles in Romania: A Comparative Clinical and Epidemiological Analysis of the 2017–2019 and 2023–2024 Epidemic Waves at a Tertiary Care Centre in Bucharest - Gheorghiță Jugulete; Mădălina Maria Merișescu; Bianca Borcos; Alexandra Nicoleta Totoianu; Anca Oana Dragomirescu (Viruses, 2025)
Measles remains a major public health issue, particularly among paediatric populations who are unvaccinated or lack of maternal antibody transfer. Although the majority of cases manifest with moderate clinical forms, certain patient categories are at risk for severe disease progression. This study aims to describe the clinical and epidemiological characteristics of paediatric measles cases hospitalized in the Paediatric Departments of the “Prof. Dr. Matei Balș” National Institute of Infectious Diseases, Bucharest, Romania during two distinct epidemic waves: 2017–2019 and 2023–2024. A retrospective analysis evaluated mortality rates, distribution by age and sex, as well as clinical disease patterns. The 2023–2024 measles epidemic was marked by a higher number of paediatric cases (3.114 vs. 1.068), a lower mortality rate (0.32% vs. 3.74%), a shift towards older age groups, and a greater frequency of complications—particularly gastrointestinal, haematological, and ophthalmological—compared to the 2017–2019 wave. The findings underscore the urgent need for strengthened vaccination programs and targeted public health interventions, particularly among vulnerable groups and patients at risk of developing severe forms of the disease. Owing to a sustained decline in measles vaccination coverage among the paediatric population, Romania has experienced two major measles outbreaks within the past decade, interrupted by the COVID-19 pandemic. This study draws attention to the increasing incidence of measles in older children, suggesting a cumulative effect of reduced immunization rates over time.